2015
DOI: 10.1021/acs.jafc.5b00125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical and Enzymatic Modifications on Starch–Oleic Acid Complex Formation

Abstract: The solubility of starch-inclusion complexes affects the digestibility and bioavailability of the included molecules. Acetylation with two degrees of substitution, 0.041 (low) and 0.091 (high), combined without or with a β-amylase treatment was employed to improve the yield and solubility of the inclusion complex between debranched potato starch and oleic acid. Both soluble and insoluble complexes were recovered and analyzed for their degree of acetylation, complexation yields, molecular size distributions, X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
7
10
0
Order By: Relevance
“…The soluble complex had a similar DS as the insoluble complex within the same treatment for both starches (Table ). The β‐amylase treatment resulted in starch with a significantly greater DS for both complexes because of the inability of β‐amylase to hydrolyze anhydroglucose units that were acetylated, agreeing with the findings of Arijaje et al and Arijaje and Wang …”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The soluble complex had a similar DS as the insoluble complex within the same treatment for both starches (Table ). The β‐amylase treatment resulted in starch with a significantly greater DS for both complexes because of the inability of β‐amylase to hydrolyze anhydroglucose units that were acetylated, agreeing with the findings of Arijaje et al and Arijaje and Wang …”
Section: Resultssupporting
confidence: 89%
“…Although their amylose contents were distinctly different, the similar distribution of acetyl groups was attributed to the rapid reaction of acetylation and the location of the acetyl groups nearby the amylopectin branching points . Under the conditions studied, soluble complexes were formed at a DS of 0.034 and 0.032 for potato starch and Hylon VII, respectively, which were lower than the DS reported for the formation of soluble complexes between acetylated potato starch and stearic (DS 0.063), oleic and linoleic acids (DS 0.048) . More planar molecules tend to be included in a greater proportion into the amylose helix, causing the complex to precipitate, hence a greater DS was required to maintain the soluble complex as demonstrated by Wulff and Kubik and Wulff et al which showed that hydroxypropylated amylose of DS 0.06–0.075 was needed to maintain soluble complexes with sodium dodecyl sulfate.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations